Pengaruh Tingkat Pendidikan Orang Tua Terhadap Prestasi Belajar Siswa di SD Islam AL Falah Bukittinggi - Mai Sri Lena; Sartono Sartono; Nia Indah Susanti; Devi Elia (Pusat Riset dan Inovasi Nasional, 2023)
The first education children get comes from their closest environment, namely the family environment, especially parents. Parental education is considered to have an influence on student learning achievement. The purpose of this study was to determine whether the level of parental education has an influence on student learning achievement at SD Islam AL Falah Bukittinggi. The method used in this research is quantitative method with simple linear regression statistical technique, with a significance level value of 5% or 0.05%. This research data was obtained by distributing questionnaires to parents to see the level of parental education and giving knowledge tests to students to measure the level of student achievement. The sample of this study were 23 students of class II of Al Falah Islamic Elementary School Bukittinggi. The results showed that grade II students of SD Islam AL Falah Bukittinggi who have high learning achievement do not always come from children who have parents with high educational backgrounds.